Studi Literatur Terpilih Mengenai Perkembangan Teori Akuntansi - Cynthia Agatha; Canita Liani; Nathalie -; Carmel Meiden (Universitas Malahayati, 2023)
This research on the development of accounting theory investigates accounting theories that are widely used by accountants in various parts of the world. Information regarding the development of accounting theory is shown as an important form of financial information that will become the basis for planning and strategic decisions. This review provides a comprehensive study of the accounting theory literature. The review focuses on research on the development of accounting theory from the last 5 years, but due to the limited number of research articles on this topic, we are expanding the scope of the year from 1999-2022. The articles are generally selected from the top accounting journals. This review offers an introduction to the methodology used in this research tradition and draws on the main results from a literature study on accounting theory from various research outcomes. Furthermore, this review describes the study of the development of accounting theory over time and shows the different accounting theories that can be compared. Overall, this review provides in-depth information on the developmental literature on accounting theory to readers wishing to become familiar with this line of empirical accounting research.